Mapping crisis intervention course into social work academic curricula in Lebanon - Rania Mansour (Open Journal of Trauma - Peertechz Publications, 2023)
Social work is strongly presented to support and decrease the suffering of people living in a crisis. The call to intervene professionally in such cases is highly demanded by government institutions, non-governmental organizations, international organizations, and United Nations agencies, the main umbrella that enfolded practitioner social workers in Lebanon. Although Lebanon has experienced successive crises for more than forty years, there is no national strategy for social work or for intervention during crises that must be developed by the Ministry of Social Affairs in collaboration with relevant institutions such as academia. However, considering that the Lebanese universities that graduate social workers are the most important source for developing that strategy based on evidence-based research, unfortunately, they did not do any action. The purpose of this article is to describe how these universities are preparing students and developing their capacities to deal with the crisis consequences. The focus of this article is the presence of the Crisis Intervention (CI) course in the curricula of universities. Data were collected from all Lebanese universities' websites and catalogs with undergraduate-level social work majors (N = 6). The data were issued from reviewing the curricula of the six universities that covered the N = 290 course. Data shows that the CI course does not enclose three out of six published curricula as well and results indicate a modest appearance of the crisis and its relevant courses. Accordingly, at the end of the research, a syllabus of the crisis intervention course is proposed and will be shared with the six Lebanese concerned Universities.